Legal Certainty In The Provision of Free Notarial Services For The Underprivileged - Syaid, Ishma Safira; Djumikasih; Trie Sulistiowarni (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
This study aims to analyze the legal consequences of incomplete norms governing the obligation to provide free notarial services by notaries to the underprivileged as stipulated in Article 37 of the Notary Law (UUJN). This provision actually reflects the social function of the notary office in ensuring access to justice. However, Article 37 of the UUJN does not yet contain clear parameters regarding the criteria for the underprivileged, the types of notarial services that must be provided, or the financing mechanism. This study uses a normative legal research method with a statutory, comparative, and conceptual approach. The results show that the incomplete norms in Article 37 of the UUJN create legal uncertainty. Based on previous field research, there are differences in the implementation of the obligation to provide free notarial services among notaries for the underprivileged. A comparative study with Law Number 16 of 2011 concerning Legal Aid and Government Regulations related to its implementation shows that the legal aid system has a more comprehensive legal framework, including parameters for beneficiaries, types of services provided, and financing mechanisms from the state. Therefore, it is necessary to establish implementing regulations or technical guidelines that detail the obligation to provide free notarial services, as explained above. This normative reconstruction is crucial to ensuring legal certainty for notaries and the beneficiary community.